(untitled) (Journal Of Educational and Psychological Researches, 2009)
Teachers’ self-efficacy plays a very important role in the process of teaching English language, and teachers have primary role in determining what is needed or what would work best with their students. The sample consists of eighty-seven English language teachers in secondary schools in Baghdad/Kaarkh2. Self-efficacy questionnaire of fifteen items was constructed. Face, content validity and reliability were verified. Then, pupils’ marks for the first semester were taken as their achievement.The main finding of the study indicates that: English language teachers’ self-efficacy has effect on their pupils’ achievement. In the light of the findings of the present study, several conclusions, recommendations and suggestions for further study have been made.